Astroglial activation and altered amyloid metabolism in human repetitive concussion - Shahim, Pashtun (Neurology, 2017)
OBJECTIVE: To determine whether postconcussion syndrome (PCS) due to repetitive concussive traumatic brain injury (rcTBI) is associated with CSF biomarker evidence of astroglial activation, amyloid deposition, and blood–brain barrier (BBB) impairment. METHODS: A total of 47 participants (28 professional athletes with PCS and 19 controls) were assessed with lumbar puncture (median 1.5 years, range 0.25–12 years after last concussion), standard MRI of the brain, and Rivermead Post-Concussion Symptoms Questionnaire (RPQ). The main outcome measures were CSF concentrations of astroglial activation markers (glial fibrillary acidic protein [GFAP] and YKL-40), markers reflecting amyloid precursor protein metabolism (Aβ38, Aβ40, Aβ42, sAPPα, and sAPPβ), and BBB function (CSF:serum albumin ratio). RESULTS: Nine of the 28 athletes returned to play within a year, while 19 had persistent PCS >1 year. Athletes with PCS >1 year had higher RPQ scores and number of concussions than athletes with PCS <1 year. Median concentrations of GFAP and YKL-40 were higher in athletes with PCS >1 year compared with controls, although with an overlap between the groups. YKL-40 correlated with RPQ score and the lifetime number of concussions. Athletes with rcTBI had lower concentrations of Aβ40 and Aβ42 than controls. The CSF:serum albumin ratio was unaltered. CONCLUSIONS: This study suggests that PCS may be associated with biomarker evidence of astroglial activation and β-amyloid (Aβ) dysmetabolism in the brain. There was no clear evidence of Aβ deposition as Aβ40 and Aβ42 were reduced in parallel. The CSF:serum albumin ratio was unaltered, suggesting that the BBB is largely intact in PCS.